COVID-19 Self-Screening in Emergency Unit Nurses - Yunita Sandy Tualaka (UrbanGreen, 2020)
Health care personnel especially in the emergency unit is most vulnerable to COVID-19 because the probability of direct contact with infected people is very high. The number of health workers who died due to COVID 19 starting from 7th May is 202 people. Objective: To know COVID-19 exposure risk to emergency unit nurses. Methods: This was descriptive quantitative research. The population was nurses working in the emergency units with 58 respondents taken with accidental sampling technique. Data were collected using questionnaires consisting of 20 questions distributed online with Google form. Results: The result shows most of the respondents have a low risk of COVID19 with a total of 56 people (96.6%) and 2 people (3.48%) have high risk. Conclusion: The majority of emergency unit nurses currently have a low exposure risk of COVID-19. Keywords: Self-screening, COVID-19, emergency unit nurses